Effect of Continuous Cropping and Fertilization on Sulphur Fractions and their Contribution to Sulphur Uptake under Rice-Wheat System in Calciorthents - and J. Prasad, A.K. Pandey, Vipin Kumar (Journal of the Indian Society of Soil Science, 2016)
The studies on long-term influence of four fertility levels and organics under rice-wheat cropping system on sulphur (S) fractions and their contribution to plant uptake have been in progress since 1988 on Calciorthents of Pusa, Bihar. Continuous application of chemical fertilizers and organic manures improved all the S fractions in soil except where organic and inorganic S was not applied. The higher fertility levels were associated with higher grain and straw yields of rice and wheat than those of lower fertility levels. Influence of different organics on grain and straw yields varied in the order: compost+crop residue > compost > crop residue > no organics. Sulphur uptake by rice and wheat increased from 3.87 to 15.87 and 2.79 to 14.92 kg ha-1, respectively with increasing levels of NPKS. Significant positive relationship amongst the different forms of S indicated the existence of equilibrium among themselves. All the S fractions exhibited significant positive relationship with yield and S uptake by rice and wheat.